Clinical safety and pharmacokinetics of a novel oral niclosamide formulation compared with marketed niclosamide chewing tablets in healthy volunteers: A three-part randomized, double-blind, placebo-controlled trial - Niklas Walther; Robert Schultz-Heienbrok; Heino Staß; Victor M. Corman; Nils C. Gassen; Marcel A. Müller; Christian Drosten; Martin Witzenrath; Hweeling Lee; Maximilian G. Posch (PLoS ONE, 2025)
Aim Niclosamide is an established anthelmintic substance and a promising candidate for treating cancer, viral infections, and other diseases. However, its solubility in aqueous media is low, and the systemic bioavailability of the commercially available chewing tablet is poor, limiting the use of niclosamide for systemic treatment. A liquid oral formulation using polyethylene glycol 400 was developed and investigated in healthy volunteers to assess safety, tolerability, and pharmacokinetics in comparison to the marketed tablet. (ClinicalTrials.gov: NCT04644705). Methods The study consisted of three parts: Part A was a double-blind placebo-controlled single ascending dose trial in three dose groups (200, 600, and 1600 mg) with four participants receiving either the investigational niclosamide formulation or placebo (3:1) under fasted and/or fed conditions. Part B was a crossover study comparing 1600 mg investigational niclosamide solution with the marketed 2000 mg chewing tablet in four healthy volunteers. Part C was a double-blind placebo-controlled multiple-dose trial comparing 1200 mg and 1600 mg (verum: placebo 4:2) in two dose groups with six subjects each, who received daily doses for seven days. Results No serious or severe adverse events occurred. The most frequent adverse events were mild to moderate gastrointestinal reactions. There was also no apparent dependence between drug exposure levels (AUC, Cmax) and the severity and incidence of adverse events detectable. A relevant food effect was observed with a mean AUC last about 2-fold higher in fed condition compared to fasted condition. In Part B, dose-normalized C max and AUC last were similar for niclosamide solution and tablet. Absorption of niclosamide solution was highly variable. Some individuals showed high absorption (C max > 2µg/ml) whereas others did absorb only marginally. Importantly, there was no dose linearity in the range of 200 mg – 1600 mg. No signs of relevant systemic drug accumulation after multiple administrations were observed. Conclusion Overall safety and tolerability observed in healthy subjects were benign. This is also true for individuals with high absorption (C max > 2µg/ml), encouraging further research into niclosamide as a potential therapeutic agent. Galenic optimization, however, will remain challenging as evident from the observed exposure variability and non-linear PK. Non-linearity, if confirmed by additional data, might make niclosamide more suitable for multi-dose rather than high single dose regimens. The observed food effect should also be considered when further investigating systemic niclosamide exposures. Trial registration ClinicalTrials.gov NCT04644705